Negotiating the legacies of intragroup violence in Timor Leste - Igreja, Victor (International journal of transitional justice, 2021)
The end of the Cold War raised the profiles of international tribunals and truth commissions as official mechanisms for dealing with the legacies of political violence around the world. However, these mechanisms have the tendency to generate somewhat stark accounts of the past and present, and of guilt and heroism, and are thus an inadequate forum for grasping the complexities of protracted, multiple and fracturing intragroup violence. This article is based on fieldwork in Timor Leste. It analyzes the unresolved legacies of Timorese intragroup political violence through a focus on the interventions of political leaders in the Timorese national parliament over time, coupled with an analysis of some of their autobiographies. It reveals how the crisscrossing histories of violence and fluctuating group affiliations have shaped ongoing political struggles, from silence and denial to unsettling voices and deliberations, which constitute sources of enduring political negotiations, mistrust and tension among Timorese leaders.